2006
DOI: 10.1016/j.mycres.2006.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the region of origin on the mycobiota of grapes with emphasis on Aspergillus and Penicillium species

Abstract: A three-year study was undertaken to investigate the fungal species present on the surface of grape berries from Portuguese vineyards in four winemaking regions. Emphasis was given to Aspergillus and Penicillium species due to their relevance for mycotoxin production. From the 3517 fungal strains detected 27 genera were identified. The region of origin markedly influenced the spoilage fungal population to which berries are exposed. The main differences found were in the incidence of A. niger aggregate, Botryis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 14 publications
8
66
3
Order By: Relevance
“…It was observed that wines from Southern Europe and North Africa, with Mediterranean climates, contained more OTA than those originating from the more temperate regions of central Europe (Otteneder & Majerus, 2000;Zimmerli & Dick, 1996). In fact, it was found that climate has an effect on the occurrence of OTA and OTAproducing fungi in grapes (Battilani, Barbano et al, 2006;Battilani, Magan, & Logdrieco, 2006;Serra, Analia, Pedro, & Venacio, 2006). The aim of this work was to survey the occurrence of OTA and to identify the ochratoxigenic moulds in Tunisian vineyards located in different viticultural regions of Tunisia with singular climate.…”
Section: Introductionmentioning
confidence: 96%
“…It was observed that wines from Southern Europe and North Africa, with Mediterranean climates, contained more OTA than those originating from the more temperate regions of central Europe (Otteneder & Majerus, 2000;Zimmerli & Dick, 1996). In fact, it was found that climate has an effect on the occurrence of OTA and OTAproducing fungi in grapes (Battilani, Barbano et al, 2006;Battilani, Magan, & Logdrieco, 2006;Serra, Analia, Pedro, & Venacio, 2006). The aim of this work was to survey the occurrence of OTA and to identify the ochratoxigenic moulds in Tunisian vineyards located in different viticultural regions of Tunisia with singular climate.…”
Section: Introductionmentioning
confidence: 96%
“…The incidence of Alternaria in grapes has been reported in different percentages with respect to total mycobiota: 5-23% in USA, 25% in Italy, 80% in Argentina; 3-18%, 24%, 17% in different studies in Portugal, 75%, 3-58%, 13% in Spain, and A. alternata and A. tenuissima were reported in 16-19% in Slovakia [7,8,13,15,24,25,[35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of Alternaria strains was isolated from different hosts including grapes [3][4][5][6]. Species such as Alternaria alternata, A. arborescens and A. tenuissima have frequently been isolated from grapes during development in the vineyard or postharvest storage [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concern about filamentous fungi in the vineyard has traditionally been linked to spoilage of grapes due to fungal growth. Two main genera are responsible for mycotoxin production in grapes: Aspergillus and Penicillium, but Aspergillus are important in hot and dry climates, where black Aspergillus, namely A. carbonarius, can lead to achratoxin A production in grapes (Serra et al, 2006). The mycotoxin production is characteristic of the species and therefore by identifying the species one can predict potential mycotoxin hazards.…”
Section: Introductionmentioning
confidence: 99%